THE ROLE OF EMOTIONAL INTELLIGENCE IN SCHOOL LEADERSHIP: A SYSTEMATIC REVIEW OF CONFLICT RESOLUTION PRACTICES - Thusi, Thandoluhle Tia; Galupo, Ellen Nove R.; Dorado, Leonardo B. (12th International Scholars Conference 2025, 2026)
This systematic review critically examines 17 empirical studies to synthesize evidence on the role of emotional intelligence (EI) competencies in determining how primary and secondary leaders manage conflicts in their schools. Utilizing thematic synthesis, three explicit competencies, emotional regulation, empathy, and self-awareness, emerged as effective when mediated through the conflict and when creating collegiality. The review also indicated some contextual influences, particularly the demographics of the leader (i.e., age, gender, and experience), which can moderate or determine EI in conflict situations. Overall, the findings of this review suggest leaders with high emotional intelligence manage to defuse tension, establish trust, and maintain organizational wellness. It was also revealed that inconsistencies across the literature, arising from studies undertaking individual, asynchronous, and non-participatory approaches, hindered the applicability of including EI in modern-day leadership preparation programs. In response, evidence-informed recommendations for incorporating EI competencies into professional development courses were generated to improve effective conflict management, enhance leadership efficacy, and develop a positive school climate. Ultimately, this review positions emotional intelligence not as an ancillary soft skill but as a core competency for transformative school leadership in the 21st century.